Erosion risk map of Samos Island using a simple probability model. - Gournelos, Th.; Evelpidou, N.; Kotinas, V. (10th International Congress of the Hellenic Geographical Society, 22-24 October, 2014)
part and the Karvouni mountain in the central part. The Geology of Samos consists of a metamorphic substratum, a non metamorphic unit, neogene and quaternary sediments. This island has been affected many times by natural hazards, such as forest fires, soil erosion, flash floods and gravity movements. The aim of this paper is to create an erosion risk map of Samos Island. This has been achieved by a series of separate stages, such as the creation of a database of geological, geomorphological and topographic data, extensive field observations and analyses of aerial photos and satellite images, within a GIS based platform. The final step involves the application of a functional relationship based on a probability model to input data consisting of the lithology, slope, mean altitude, and the vegetation-land use for each drainage basin to produce the final erosion risk map.